Upper body contributions to pitched ball velocity in elite high school pitchers using an induced velocity analysis - Alderink, G. J.; Kepple, T.; Stanhope, S. J.; Aguinaldo, A. (Journal of Biomechanics, 2021)
Interest in joint and segment contributions to pitched ball velocity has been dominated by inverse dynamic solutions, which is limited in ascertaining complex muscle/joint interactions. Our purpose was to use induced velocity analysis to investigate which joint(s) made the largest contribution to the velocity of a pitched ball. Pitching data were collected from six elite high school-aged pitchers with no history of arm injury. Participants threw a fastball pitch from the windup on flat ground. Data were collected using seven Vicon 612 cameras (250 Hz) and three AMTI force platforms (1000 Hz). A 14-segment biomechanical model (feet, legs, thighs, pelvis, a combined thorax-abdomen-head, i.e., trunk, upper arms, forearms, and hands) was implemented in Visual3D as a dynamic link library built using SD/Fast (PTC) software. Model-generated induced velocity of the ball was validated against ball velocity obtained from a calibrated radar gun. Velocity induced torques at the shoulder just prior to release, and elbow during the cocking phase, contributed 31.0% and 18.1%, respectively, to forward ball velocity. The centripetal/Coriolis effects from the upper arm and forearm velocities made the largest contribution to ball velocity (average 57.8%), but the source of these effects are unknown. The lower extremities and trunk made little direct contribution to pitched ball velocity. These results may have implications with regard to pitching performance enhancement and rehabilitation.